Filaggrin and Atopic Dermatitis: Clinical and Pathogenetic Parallels and Therapeutic Possibilities - Nikolay N. Murashkin; Roman A. Ivanov; Eduard T. Ambarchian; Roman V. Epishev; Alexander I. Materikin; Leonid A. Opryatin; Alena A. Savelova ("Paediatrician" Publishers LLC, 2021)
Atopic dermatitis (AtD) is multifactorial inflammatory skin disease, one of the aspects of its pathogenesis is epidermal barrier dysfunction. Early development of AtD is associated with filaggrin dysfunction. Filaggrin is a protein involved in aggregation of keratin filaments in the upper layers of epidermis and the retention of lipids and proteins between corneocytes. Frequently, filaggrin dysfunction can be accompanied with secondary infection and high risk of other allergic diseases development. This can happen due to disturbance in terminal differentiation of epidermal cells and, as consequence, malfunction of epidermal barrier. Thus, the long regular use of emollients is the basis of AtD therapy. New class of emollients ("emollents plus") allowed us to achieve more significant treatment results in patients with AtD. These emollients reduce inflammatory process activity in the skin by replacing structural components of abnormal epidermal barrier.